ОПІОЇДНІ РЕЦЕПТОРИ (World Science, 2020)
The aim of our work was to study scientific information and to systematize data of domestic and foreign literature concerning the study of opioid receptors. The study of receptors localization and action is a promising and very complex task.Evidence of the complex effect of each group of receptors on the body is the fact that even those drugs that have a chemical structure in common with morphine, each have their own characteristics in the spectrum of action, side effects, the ability to pass the blood-brain barrier, efficacy and duration of anesthesia, addictive properties and other. This is eplained due to that the effect on receptors depends not only on the primary action of the drug, but also on the particular metabolism of a particular drug, since metabolites can be just the main factors influencing opioid receptors. In this context, it is important to note the huge number of factors that can change the duration and effectiveness of opioids, which involves a deep knowledge of this issue.Such differences partly explain th epecularity and characteristics of each opioid medication in terms of efficacy and duration of action, toxic inflance on the body, risk of complications and the occurrence of withdrawal effects, as well as particularities of use in patients with hepatic and renal impairment.